2022
DOI: 10.31234/osf.io/qw5xv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Creation of a Short-Form and Brief Short-Form Version of The Coping with Children’s Negative Emotions Scale

Abstract: The current study evaluated the theoretical alignment between the Coping with Children's Negative Emotion Scale (CCNES), a commonly used measure to asses parent emotion socialization, and Gottman, Katz and Hooven’s meta-emotion theory. Further, we created an 18-item short-form (3 emotion coaching subscales, 3 emotion dismissing subscales), and 6-item brief short-form (emotion coaching subscale and emotion dismissing subscale) with acceptable psychometric properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Hajal and Paley (2020) argue that for emotion socialization research, measures which assess 'parent-specific' emotion regulation should be prioritized. While Hajal and Paley (2020) posit that the distress reactions subscale of the Coping with Children's Negative Emotions Scale (Yagmurlu andAltan, 2009, Hajal andPaley, 2020) is a viable assessment of parents' emotion regulation, there is evidence of poor construct validity for this subscale (King, 2022). Nevertheless, we found that the short-form distress reactions subscale differentiated parents' emotion regulation as expected, which has a more parsimonious set of items compared to the original subscale (King, 2022).…”
Section: P R E P R I N Tmentioning
confidence: 51%
See 2 more Smart Citations
“…Hajal and Paley (2020) argue that for emotion socialization research, measures which assess 'parent-specific' emotion regulation should be prioritized. While Hajal and Paley (2020) posit that the distress reactions subscale of the Coping with Children's Negative Emotions Scale (Yagmurlu andAltan, 2009, Hajal andPaley, 2020) is a viable assessment of parents' emotion regulation, there is evidence of poor construct validity for this subscale (King, 2022). Nevertheless, we found that the short-form distress reactions subscale differentiated parents' emotion regulation as expected, which has a more parsimonious set of items compared to the original subscale (King, 2022).…”
Section: P R E P R I N Tmentioning
confidence: 51%
“…Emotion-related parenting practices. Parent-reported emotion-related parenting practices were measured with six subscales from the short-form Coping with Children's Negative Emotions Scale (King, 2022): 1) punitive reactions, i.e., parent's punitive and controlling behaviors/threat of punishment (3 items, α = .78); 2) minimization reactions, i.e., parent's minimization of emotions and derogative comments (3 items, α = .80); 3) distress reactions, i.e., parent's emotion dysregulation and distress (3 items, α = .78 ); 4) expressive encouragement, i.e., parents' encouragement of the experience and expression of emotions (3 items, α = .85); 5) empathy, i.e., parental empathy of children's emotions (3 items, α = .81); 6) problem-solving, i.e., parents' problem-solving to help manage the situation that led to children's negative emotions (3 items, α = .65). In addition, we included three items with high factor loadings from the emotion-focused responses subscale of the Coping with Children's Negative Emotions Scale (described as 'emotion distraction' in the current paper) that were excluded from the short-form Coping with Children's Negative Emotions Scale: 7) emotion distraction, i.e., i.e., where parents may be warm/comforting, but distract children from their emotions (3 items, α = .65).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation